ZBP1 mediates interferon-induced necroptosis - Yang, Daowei; Liang, Yaoji; Zhao, Shubo; Ding, Yan; Zhuang, Qiuyu; Shi, Qilin; Ai, Tingting; Wu, Su-Qin; Han, Jiahuai (Cellular & molecular immunology, 2020)
Interferons (IFNs) play an important role in immunomodulatory and antiviral functions. IFN-induced necroptosis has been reported in cells deficient in receptor-interacting protein kinase 1 (RIPK1), Fas-associated protein with death domain (FADD), or caspase-8, but the mechanism is largely unknown. Here, we report that the DNA-dependent activator of IFN regulatory factors (ZBP1, also known as DAI) is required for both type I (β) and type II (γ) IFN-induced necroptosis. We show that L929 fibroblast cells became susceptible to IFN-induced necroptosis when RIPK1 , FADD , or Caspase-8 was genetically deleted, confirming the antinecroptotic role of these proteins in IFN signaling. We found that the pronecroptotic signal from IFN stimulation depends on new protein synthesis and identified ZBP1, an IFN-stimulated gene (ISG) product, as the de novo synthesized protein that triggers necroptosis in IFN-stimulated cells. The N-terminal domain (ND) of ZBP1 is important for ZBP1–ZBP1 homointeraction, and its RHIM domain in the C-terminal region interacts with RIPK3 to initiate RIPK3-dependent necroptosis. The antinecroptotic function of RIPK1, FADD, and caspase-8 in IFN-treated cells is most likely executed by caspase-8-mediated cleavage of RIPK3, since the inhibitory effect on necroptosis was eliminated when the caspase-8 cleavage site in RIPK3 was mutated. ZBP1-mediated necroptosis in IFN-treated cells is likely physiologically relevant, as ZBP1 KO mice were significantly protected against acute systemic inflammatory response syndrome (SIRS) induced by TNF + IFN-γ.